Contributions of the Law and Order Towards the Proliferation of Muslim Ideologies in The United States of America - Adesokan, Abdurrahman Toyese; Yusof, Abdullah; Ali Mat Zin, Aizan (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2023)
Law and order of the United States of America play tremendous role towards the proliferation of Muslims ideologies. Muslims benefits from the Law of the land that permits the believers to practice their religion and its tenets freely and Islam disallow the Muslims to go against the law of the land so far it allows them to practice their religion. It has been normal for the Muslims in America to enjoy the same opportunity of the protection and security that the Jews, Gentiles and the Christians enjoy in the States. This has been the case since 1786 when Thomas Jefferson recounted his satisfaction with the state of Virginia’s landmark bill for establishing religious freedom that was passed by then. The friendly neighborhood that Islam encouraged made it applicable to American law. Houston Congress-man Al-Green supported Islam been a friendly religion, condemning atrocity of labelling Islam with terrorism, defending this course in the congress of America by saying: “I stand here to support Islam today, one of the great religions of the world. He said: to demean Islam by adding the world terrorist with it is an injustice to the religion” (Record, 2015). President Thomas Jefferson’s recognition of the Ramadan iftar in 1805 proved that the American Founding Fathers appreciated the existence of Islam in their domain since then and it continued till today (Wang, 2017). This work will showcase many of the American Law and Order in favor of Islam and the Muslims. The result will clear America as a safe place for moderate and obedient Muslims.